IMPLIKATUR PERCAKAPAN DALAM DEBAT PASANGAN CALON BUPATI DAN WAKIL BUPATI SAMBAS TAHUN 2020 - Puji Febriyani; Patriantoro Patriantoro; Ahmad Rabi’ul Muzammil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to describe the forms and types of conversational implicatures in the 2020 Sambas Regent and Deputy Regent Candidate Debate. The research method used is descriptive with a qualitative research form. The data from this study are declarative sentences, imperative sentences, introgative sentences, general and specific conversational implicature in the 2020 Sambas Regent and Deputy Regent Candidate Pair Debate. The source of data was taking from the 2020 Sambas Regent and Deputy Regent candidate pair debate which is broadcast through the Sambas Regency Comunications and Information Agency youtube page which was broadcast live on November 21, 2020, lasted 3 hours 26 minutes 25 detik. The data collection technique in this research is a documentary study technique. Based on the results of the analysis in the 2020 Sambas regent and Deputy Regent Candidate Debate, it can be concluded that there are 23 forms af declarative implicature sentences, 21 forms of interrogative implicature sentences, 41 forms of imperative implicature sentences, 7 forms of general conversational implicature sentences, and 78 specific conversational implicature sentences. In addition, this research can also be used as teaching material in learning Indonesian for grade X second semester in senior high school level as the debate material.Keywords: Conversational Implicature, Debate, Implicatur